2020
DOI: 10.3390/molecules25030710
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Optimization, Structural Characterization, and Anticoagulant Activity of Acidic Polysaccharides from Auricularia auricula-judae

Abstract: To explore Auricularia auricula-judae polysaccharides (AAP) as natural anticoagulants for application in the functional food industry, ultrasound assisted extraction (UAE) was optimized for the extraction of AAP by using a response surface methodology (RSM). The maximum extraction yield of crude AAP (14.74 mg/g) was obtained at the optimized extraction parameters as follows: Extraction temperature (74 °C), extraction time (27 min), the ratio of liquid to raw material (103 mL/g), and ultrasound power (198 W). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Besides possessing proteins and minerals, Auricularia auricula largely contains carbohydrates. The recent reports have shown that A. auricula extract exhibited antioxidant activity and promoted procollagen biosynthesis [ 13 ], antitumor activities [ 14 ], and anticoagulant activity [ 15 ]. However, the medicinal properties of A. auricula-judae as a wound-healing agent has not yet been fully elucidated, as only a few studies have been conducted so far.…”
Section: Introductionmentioning
confidence: 99%
“…Besides possessing proteins and minerals, Auricularia auricula largely contains carbohydrates. The recent reports have shown that A. auricula extract exhibited antioxidant activity and promoted procollagen biosynthesis [ 13 ], antitumor activities [ 14 ], and anticoagulant activity [ 15 ]. However, the medicinal properties of A. auricula-judae as a wound-healing agent has not yet been fully elucidated, as only a few studies have been conducted so far.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional use of this mushroom as an agent in blood vessel purification ( Table 1 ) may have recently found its scientific support. According to Bian et al [ 28 ], fruiting bodies of mushroom are a source of acidic polysaccharides with glucuronide (defined as aAAP-1), which exhibited anticoagulant activity. As confirmed by Yoon et al [ 29 ], polysaccharides from this mushroom are those with anticoagulant activity due to catalysis of thrombin inhibition by antithrombin, with glucuronic acid being the essential factor for this polysaccharide activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is important that the extraction process should be optimised to maintain the pharmacological activities of AAP (Cai et al 2015;Bian et al 2020). Gu et al (2021) found that when ultrasonic power was 130 W, there was a significant difference from the other four groups in the yield of AAP (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, conducting comparative studies of different extraction methods of AAP with different molecular weights and lipid-lowering activities is of particular importance. At present, the main extraction method of AAP is hot water extraction (Cai et al 2015), ultrasound treatment (Wang et al 2019), ultrasound-assisted extraction (Bian et al 2020), enzymatic extraction (Yue et al 2019), etc. However, there are few reports on the hypolipidaemic activity of AAP determined by different extraction methods.…”
mentioning
confidence: 99%